Combination of 1H NMR and chemometrics to discriminate manuka honey from other floral honey types from Oceania. (15th February 2017) - Spiteri, Marc; Rogers, Karyne M.; Jamin, Eric; Thomas, Freddy; Guyader, Sophie; Lees, Michèle; Rutledge, Douglas N.
Highlights: A collection of more than 250 authentic honeys from Oceania were analysed through NMR. Quantification of three markers has been done simultaneously on all these honeys. Determination of the botanical origin have been done using chemometrics. The methodology can be implemented for routine use in food control laboratory. Abstract: Manuka honey is a product produced essentially in New Zealand, and has been widely recognised for its antibacterial properties and specific taste. In this study, 264 honeys from New Zealand and Australia were analysed using proton NMR spectroscopy coupled with chemometrics. Known manuka markers, methylglyoxal and dihydroxyacetone, have been characterised and quantified, together with a new NMR marker, identified as being leptosperin. Manuka honey profiling using 1H NMR is shown to be a possible alternative to chromatography with the added advantage that it can measure methylglyoxal (MGO), dihydroxyacetone (DHA) and leptosperin simultaneously. By combining the information from these three markers, we established a model to estimate the proportion of manuka in a given honey. Markers of other botanical origins were also identified, which makes 1H NMR a convenient and efficient tool, complementary to pollen analysis, to control the botanical origin of Oceania honeys.